Implementation of the Pancasila Student Profile Strengthening Project in Early Childhood Character Development - Said Ashlan (Pt. Anagata Sembagi Education, 2026)
This study examines the implementation of the Pancasila Student Profile Strengthening Project (Projek Penguatan Profil Pelajar Pancasila, P5) in early childhood character development under Indonesia's Kurikulum Merdeka. Using a systematic literature review of 25 peer-reviewed articles published between 2021 and 2025, the study synthesizes empirical findings on how early childhood education institutions design, implement, and evaluate P5 activities to cultivate six core character dimensions: faith and piety toward God, global diversity, mutual cooperation (gotong royong), independence, critical reasoning, and creativity. The review shows that successful implementation depends on contextualized, play-based, and locally rooted project themes; teachers acting as facilitators rather than instructors; and structured collaboration among schools, families, and communities. Recurring obstacles include limited teacher understanding of project-based planning and assessment, restricted time and resources, and uneven integration of local cultural values into project themes. The review further identifies an underexplored area in the literature: the differentiated design of P5 specifically for learners aged 0-6, as distinct from primary and secondary applications. By consolidating findings across educational levels and regions, this article offers a novel, age-specific synthesis linking project-based learning, Pancasila values, and developmentally appropriate practice, and provides practical implications for early childhood educators, school leaders, and policymakers seeking to strengthen character formation through experiential and culturally grounded projects